Pengaruh Citra Merek, Kepercayaan dan Kepuasan Pelanggan terhadap Loyalitas Pelanggan Honda Astra Motor Sako Palembang - Mulia, Edo Saputra; Widagdo , Herry (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the effect of brand image, trust, and customer satisfaction on customer loyalty at Honda Astra Motor Sako Palembang. This study uses a quantitative approach with a descriptive method. Data were collected through questionnaires given to 319 respondents as research samples. The sampling technique used a non-probability sampling method with a purposive sampling approach. For data analysis using multiple regression with the help of SPSS-26 software. Based on the results of the study, the results showed that the partial test of the variables), Brand Image , Trust , and Customer Satisfaction had a positive and significant effect on Customer Loyalty both individually (partial) and together (simultaneously) at Honda Astra Motor Sako Palembang.